Guiding Strategies for the Future of Vascularized Composite Allotransplantation: A Systematic Review of Organ Donation Campaigns. Issue 4 (October 2020) - Mills, Emily; Felsenheld, Julia H.; Berman, Zoe P.; Alfonso, Allyson R.; Diep, Gustave K.; Wolfe, Erin M.; Park, Jenn J.; Hoffman, Alexandra F.; Ramly, Elie P.; Rodriguez, Eduardo D.
Abstract : Background: Since the 1990s, the field of vascularized composite allotransplantation has gained momentum, offering unprecedented solutions for patients with defects not amenable to autologous reconstruction. As with solid organ donation, the vascularized composite allotransplant donor pool remains limited. This systematic review identifies past successes and failures in organ donation campaigns to guide future strategies for expanding vascularized composite allotransplant donation. Methods: A systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Three databases (PubMed/MEDLINE, PsycINFO, and Embase) were searched through July 31, 2019. The study compiled solid organ and vascularized composite allotransplant campaigns that aimed to increase donor registration. Articles depicting the current state of vascularized composite allotransplant donation were also assessed. Results: Of an initial 3318 articles identified, 40 were included. Six articles described direct mail or print interventions, 10 depicted Web-based interventions, 13 dealt with interpersonal interventions, and seven used multimodal interventions. Four articles described the current state of vascularized composite allotransplant donation. A qualitative synthesis was conducted. The authors found that social media campaigns can have a robust but fleeting effect on registration trends and that interpersonal interventions are effective at increasing registration rates. In addition, the opportunity for participants to immediately register as organ donors, by means of either return mail, in-person, or online, is vital to campaign success. Conclusions: Public organ donation campaigns have had success in increasing organ donor registration rates, particularly through the use of social media and interpersonal interventions that allow for immediate registration. Synthesizing this information, we propose a multimodal campaign to expand the vascularized composite allotransplant donor pool.